Shaping rural Areas in Europe : perceptions and outcomes on the present and the future - Figueiredo, Elisabete; Silva, Luis (GeoJournal Library, 2013)
Shaping Rural Areas in Europe. Perceptions and Outcomes on the Present and the Future sets out to investigate the effect of urban perceptions about the rural and consequent demands on rurality on the present and future configurations of rural territories in Europe in the early twenty-first century. This volume presents and discusses a broad range of case studies and theoretical and methodological approaches from different academic fields, mainly Anthropology, Sociology and Geography.